The mechanical properties of braided reinforced composites for application in concrete structures - Fangueiro, Raúl (2006)
The current work is concerned with the development of braided reinforced composites for civil engineering applications. The research study aims at understanding the mechanical behaviour of core reinforced braided fabrics. Various samples have been produced using polyester fibres, for the production of the braided fabrics, and glass, carbon, polyethylene and sisal fibres, for the core reinforcement. The results of the tensile tests carried out in the various samples of reinforced braided fabrics obtained are presented and discussed. Moreover, the influence of the testing conditions and of the braiding angle are also studied. In order to produce braided reinforced composite rods to be used as concrete reinforcement, a special technique has been developed using a standard vertical braiding machine. The tensile and bending properties of braided reinforced composite rods have been evaluated and the results obtained are presented, discussed and compared with those of conventional materials, such as steel.